2D Jet scour - Lim, Yet Hun (Nanyang Technological University, 2019)
Studies on scour had begun since 1939. Scouring in the vicinity of hydraulic structures are not desirable as it brings instability to the affected structures and danger to users. Two-dimensional (2D) jet scour studies first started in order to understand the nature of scour. A thorough literature review was carried out to understand the nature and types of scour that are identified up to date. Studies for developing equations to predict scour have been ongoing for a while. However, every prediction model developed had their limitations, thus studies on developing prediction models have been ongoing. Hydraulic parameters have been studied to understand their effects towards scour and to identify ways to reduce scour, the length of apron has shown to reduce the effects of scour as the length increases. Prediction models for scour are developed using regression analysis with the application of self-similarity approach or through understanding the correlation of each hydraulic parameter to the depth of scour to develop a prediction model. There are two kinds of self-similarity approach, complete self-similarity and incomplete self-similarity, with most equations developed using the complete self-similarity approach. In this study, 2D jet scour will be studied using the incomplete self-similarity approach and propose a prediction model for predicting maximum scour depth. An existing database of 488 experimental data was used and analysed to develop a prediction model using the incomplete self-similarity approach. The densimetric Froude Number, F0,d84 based on the diameter size, d84, was the main parameter, and the tailwater H/d0 and sediment size, d50/d0 are the inter-related parameters to the main F0,d84 in the incomplete similarity analysis. For 2-D jet scour with an installed downstream apron, the length of apron, L is known to reduce the effects of scouring. An apron length term, (1+L/d0), where d0 is jet diameter, was used as a correction factor to account for the reduction of the scour effect with an apron protection installed. The proposed equation agrees reasonably well with the 2-D jet scour database used, and is recommended to predict the maximum scour depth for 2D jet scour under a wide range of varying sediment sizes and submerged tailwater conditions.